Mild hypoxia in vivo regulates cardioprotective SUR2A: A role for Akt and LDH - Mohammed Abdul, Khaja Shameem (Biochim Biophys Acta, 2015)
High-altitude residents have lower mortality rates for ischaemic heart disease and this is ascribed to cardiac gene remodelling by chronic hypoxia. SUR2A is a cardioprotective ABC protein serving as a subunit of sarcolemmal ATP-sensitive K(+) channels. The purpose of this study was to determine whether SUR2A is regulated by mild hypoxia in vivo and to elucidate the underlying mechanism. Mice were exposed to either 21% (control) or 18% (mild hypoxia) oxygen for 24 h. Exposure to 18% oxygen did not affect partial pressure of O(2) (PO(2)) and CO(2) (PCO(2)) in the blood, haematocrit or level of ATP in the heart. However, hypoxia increased myocardial lactate dehydrogenase (LDH) and lactate as well as NAD(+) without affecting total NAD. SUR2A levels were significantly increased as well as myocardial resistance to ischaemia–reperfusion. Exposure to 18% oxygen did not phosphorylate extracellular signal regulated kinases (ERK1/2) or AMP activated protein kinase (AMPK), but it phosphorylated protein kinase B (Akt). An inhibitor of phosphoinositide 3-kinases (PI3K), LY294002 (0.2 mg/mouse), abolished all observed effects of hypoxia. LDH inhibitors, galloflavin (50 μM) and sodium oxamate (80 mM) significantly decreased levels of SUR2A in heart embryonic H9c2 cells, while inactive mutant LDH form, gly193-M-LDH increased cellular sensitivity towards stress induced by 2,4-dinitrophenol (10 mM). Treatment of H9c2 cells with sodium lactate (30 mM) increased intracellular lactate, but did not affect LDH activity or SUR2A levels. We conclude that PI3K/Akt signalling pathway and LDH play a crucial role in increase of cardiac SUR2A induced by in vivo exposure to 18% oxygen.